Design of high‐order sliding mode controller under asymmetric output constraints - Mei, Keqi; Ma, Li; Ding, Shihong (International journal of robust and nonlinear control, 2021)
This article is devoted to the design issue of high‐order sliding mode (HOSM) controller subject to asymmetric output constraints. A barrier Lyapunov function (BLF) is first developed to deal with the constraints. Subsequently, by implanting the BLF into the modified adding a power integrator technique, a HOSM control algorithm, which is able to handle the closed‐loop system simultaneously with and without asymmetric output constraints, has been presented. It has been shown on the basis of the rigorous mathematical proof that under the proposed control strategy, the finite‐time stability of the considered system with the asymmetric output constraints is ensured. Meanwhile, the proposed algorithm also satisfies the requirement of the preset asymmetric output constraint. At last, an illustrative example is given to demonstrate the effectiveness of the presented algorithm.